Communication challenges in private finance initiative projects at the facilities management stage / Kumalasari Kipli ... [et al.] - Kipli, Kumalasari; Sidek, Norazizah; Mustapa, Fara Diva; Syed Jamaludin, Shariffah Zatil Hidayah; Zaini, Favilla (UiTM Press, 2022)
Facilities management is one of the scopes of work under the Private Finance Initiative Projects. The success of the facilities management work depends on various factors and communication is among the major factors. This paper will highlight the challenges faced during the communication between the client and facilities management managers in UiTM projects', and ways to overcome the challenges. The research was carried out using the qualitative method. The interviews were done with the engineers and facilities managers. The interviews identified the challenges as communication breakdown, human error, lack of understanding, time-consuming, and misunderstanding. These strategies are being used to clarify the root cause of the lack of understanding and resolve disputes. The following item suggested being done by the respondents; verification from the end-user, conducting a technical meeting, following the procedure in executing works and having a good relationship between both parties. Besides, to ensure smooth communication when conveying information during the operational and maintenance were suggested to use the mobile application, integrated system, roles of the concessionaire in understanding the Concession Agreement, minimize human error and improvement of CFMS, and preferably direct communication using instant messages.